Exploring indigenous entanglements in extension, land, and agriculture: an Oklahoma case study - Hayman, Jann S. (Kansas State University, 2021)
There is an extensive and complex history of agricultural and educational systems within the United States. Indigenous peoples maintained highly developed agricultural systems prior to colonization. After colonization, Indigenous and European systems converged in a battle of power that lasted for centuries. Today, there are 573 federally recognized Native nations in the United States (Bureau of Indian Affairs, 2019) and 39 federally recognized Native nations within the state of Oklahoma (Oklahoma Historical Society, n.d.). The agricultural history of each tribe is unique and European influence is found throughout. This research focuses on the agricultural history and current agricultural systems and educational programs of four Oklahoma-based Native nations: the Choctaw Nation, Muscogee (Creek) Nation, Osage Nation, and Quapaw Nation. Additionally, the study looks at educational opportunities created by the College of the Muscogee Nation. This study seeks to understand the histories of these five settings related to the development of agriculture, specifically as it relates to agricultural education. Using TribalCrit (Brayboy, 2005; Daniels, 2011; Writer, 2008) and Osage ribbon work (Dennison, 2012; Hayman, RedCorn, & Zacharakis, 2018; RedCorn, 2016; RedCorn, in press) as the theoretical frameworks, this multiple-case study seeks to understand the complex entanglements that not only existed historically, but currently exist in respect to the development of Indigenous specific agricultural education programs.
Keywords: Indigenous agriculture; Agricultural education; Native nation agricultural education